(untitled) (Research, Society and Development, 2020)
Aim: To analyze the influence of virtual rehabilitation with the X-Box® on the risk of falling in the elderly. Methodology: Quasi-experimental, descriptive-analytical, cross-sectional and quantitative study. It was composed of 30 elderly people who were 60 years old or older and of both sexes; and, excluded, those comorbidities that interfere with function and mobility and/ or cognitive changes and with terminal illnesses. It was applied the Informed Consent Form and was collected the sociodemographic and clinical data. In the evaluation were used: Berg Balance Scale (BSE), Timed Up & Go (TUG), Tinetti Test, and Wii Balance Board® platform (WBB) before and after intervention. Five interventions were carried out with the X-box® Kinect using the Dance Central Spotlight game, each lasting 30 min; and, at the end, a descriptive and statistical analysis was performed. Results: The female predominance study (83.3%), with an average age of 68.4 ± 6.8 years and a Body Mass Index of 26.1 ± 4.7 Kg / m2 (overweight). After the intervention, there was an increase in the BSE score (from 48.1 ± 5.1 to 52.4 ± 3.5) and an improvement on elderly’s balance. In the Tinetti test, there was a modification from moderate to low risk of falling (from 23.2 ± 3.5 to 25.5 ± 2.6); and in TUG, an improvement in mobility with a reduction in the test time (from 15.3 ± 4.1 to 12.8 ± 3.1 seconds). In WBB, a more proportional weight discharge was observed after the intervention, however, not statistically significant. Final Considerations: In this research, beneficial results were observed in the use of virtual reality with the X-box® as therapy in the risk of elderly falling.